Transcriptional up-regulation of host-specific terpene metabolism in aphid-induced galls of Pistacia palaestina. (15th June 2021) - Davidovich-Rikanati, Rachel; Bar, Einat; Hivert, Gal; Huang, Xing-Qi; Hoppen-Tonial, Carolina; Khankin, Vered; Rand, Karin; Abofreih, Amal; Muhlemann, Joelle K; Marchese, José Abramo; Shotland, Yoram; Dudareva, Natalia; et al.
Abstract: Galling insects gain food and shelter by inducing specialized anatomical structures in their plant hosts. Such galls often accumulate plant defensive metabolites protecting the inhabiting insects from predation. We previously found that, despite a marked natural chemopolymorphism in natural populations of Pistacia palaestina, the monoterpene content in Baizongia pistaciae -induced galls is substantially higher than in leaves of their hosts. Here we show a general up-regulation of key structural genes in both the plastidial and cytosolic terpene biosynthetic pathways in galls as compared with non-colonized leaves. Novel prenyltransferases and terpene synthases were functionally expressed in Escherichia coli to reveal their biochemical function. Individual Pistacia trees exhibiting chemopolymorphism in terpene compositions displayed differential up-regulation of selected terpene synthase genes, and the metabolites generated by their gene products in vitro corresponded to the monoterpenes accumulated by each tree. Our results delineate molecular mechanisms responsible for the formation of enhanced monoterpene in galls and the observed intraspecific monoterpene chemodiversity displayed in P. palaestina . We demonstrate that gall-inhabiting aphids transcriptionally reprogram their host terpene pathways by up-regulating tree-specific genes, boosting the accumulation of plant defensive compounds for the protection of colonizing insects. Abstract : We identified specific host plant genes responsible for the enhanced terpene biosynthesis and monoterpene chemodiversity observed in insect-induced galls, providing chemical defenses for the gall inhabitants.